Pengaruh Rasio Profitabilitas Terhadap Harga Saham Pada Industri Pertambangan Batubara Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2013-2017 - Lisnawati Lisnawati (Science of Management and Students Research Journal (SMS), 2019)
This study consisted of independent variables, namely the ratio of profitability and dependent variables, namely stock prices. The formalutions of the problem of how to influence the independent variables in dependent variables simultaneously and partially. In this study, the analytical tool used is a statistical analysis tool that consists of multiple linier regression, classical assumption test used normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, hupothesis testing and test coefficient of determination. The results of research assited by SPSS 20 devices, regression Y = 1025,457 – 36,851 X1 – 31,842 X2 + 65,508 X3 + e resulted in the other side simultaneously obtained the independent variable test (profitability ratio) having a significant effect on the dependent variable (stock price). Marked by Fcount > Ttable which is 4,198 > 3,03. For independent influence and some have significant influence on stock price. The independent variable profitability ratio) can effect the dependent variable (stock price) with a value of R 0,612 R Square with 0,375 equal to 37,5%. The conclusion obtained from the F test (simultaneous) is the independent variable profitability ratio (GPM,OPM and NPM) has a significant influence on the dependent variable stock price. Where as for the t test (Partial) OPM does not have a significant effect on stock price, and for GPM and NPM has a significant influence on the dependent variabel of stock prices.